Regulating contaminated land in order to identify, manage and cause the rehabilitation of contaminated land: a review of the legislative adequacy of South Africa's contaminated land regime - Muller, Heinrich (Department of Public Law, 2021)
Land contamination remains a chronic threat to environmental integrity and human health, warranting scrutiny on the effectiveness of the domestic legal regime. South Africa has still to understand the full extent to which it will undermine the country's sustainable development goals and well-being of its population. Contaminated land impacts not only the environment, but it causes socio-economic impacts. In 2009, the National Environmental Management: Waste Act, 2008 (Act No. 59 of 2008) was enacted with a dedicated contaminated land regime (Part 8 of that Act). Given the importance of regulating contaminated land, a valuable analysis would be to determine whether Part 8 is legislatively adequately to enable the identification, management and rehabilitation of contaminated land. There is, however, a serious lack of information about the extent of land contamination in South Africa. This is evident from its the government's official reporting. There is also little information about the enforcement of the contaminated land regime itself and it is therefore difficult to measure its success. International studies have identified certain legislative best-practice elements for contaminated land regimes. These elements present a good yardstick against which to measure Part 8 of the Waste Act for purposes of determining whether it will enable the identification, management and rehabilitation of contaminated land. This study finds that while Part 8 contains some of the legislative best practices, it mostly falls short and various reforms are recommended.